Social control in SUS management: structural, organizational and strategic aspects (Research, Society and Development, 2022)
The inclusion of the population in the definition of public health policies is considered a device for the consolidation of participatory democracy, in which it represents the realization of one of the principles of the SUS. The objective was to analyze the functioning, structure and organization of social control in the management of the SUS. This is an integrative review based on the PICo strategy, which contributed to the elaboration of the guiding question and selection of descriptors in DeCS, Emtree and MeSH. The search in the Lilacs, PubMed, Embase, Scopus and Web of Science databases took place in November 2020, considering the complete articles, published from the creation of the SUS until 2020, in Portuguese, Spanish and English, and which were not duplicated. Sixty-six articles were selected that dealt with the organizational, structural and operational aspects of collegiate bodies for social control and participatory management, which reflect on the development of their practices, highlighting the experiences of Health Councils with regard to training strategies for its members. Such experiences maximize the consolidation of a citizen and critical conscience, also favoring the different collective subjects an effective and quality participation, materializing itself as a legitimate tool of public management.